2012
DOI: 10.1021/jp301124z
|View full text |Cite
|
Sign up to set email alerts
|

Are Micelles Needed to Form Methane Hydrates in Sodium Dodecyl Sulfate Solutions?

Abstract: The possibility that methane hydrates form in sodium dodecyl sulfate (SDS) water solutions without the help of micelles formation has been investigated. To asses whether micelles are needed for the hydrate to form only one SDS molecule has been considered. To figure out the possible mechanism through which the SDS promotes the formation of methane clathrate the dynamics of CH(4) solvation in the presence and absence of the surfactant molecule is monitored. To carry out the dynamical calculations, the SDS-H(2)O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 54 publications
4
43
0
Order By: Relevance
“…reported concentration of 500 ppm for CMC of SDS in contact with methane . However, the micelles formation postulate was refuted by other researchers later . Watanabe et al .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…reported concentration of 500 ppm for CMC of SDS in contact with methane . However, the micelles formation postulate was refuted by other researchers later . Watanabe et al .…”
Section: Introductionmentioning
confidence: 94%
“…investigated the hydrate formation mechanism by using potential energy surface model in a molecular dynamic simulation study with and without SDS. Their result showed that micelles formation could not be the correct mechanism of hydrate promotion effect of SDS . Although the promotion mechanism of SDS in hydrate formation process still is not clear, visual observation showed that in the presence of SDS, hydrate crystals tend to move forward to the reactor's wall .…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in the acceleration effect of SC 12 S observed for the high initial CO 2 fractions in the gas phase might also result from a distortion of the SC 12 S molecular geometry induced by its interaction with CO 2 . Alberti et al (2013) demonstrated using molecular dynamics calculations that, in the presence of CO 2 molecules, the shape of the SC 12 S molecule changes ("it folds to form a kind of helix") but this deformation does not happen in the presence of CH 4 molecules (Alberti et al, 2012). Their MD calculations showed that the distortion of SC 12 S molecular geometry hinders the formation of clathrate-like structures from CO 2 water clusters.…”
Section: Effect Of the Surfactant Carbon-chain Length And Gas-phase Cmentioning
confidence: 99%
“…The enhanced hydrate nucleation could be due to a favorable arrangement of the water molecules around the SC 12 S molecules Lo et al,2012). It has been demonstrated that SC 12 S micelles are not needed to boost hydrate nucleation (Watanabe et al, 2005a;Zhang et al, 2007a;Alberti et al, 2012). In fact, the temperatures used to form hydrates are in most cases away below the Krafft temperature of SC 12 S. At these temperatures, SC 12 S molecules cannot form micelles, even if the SC 12 S concentration in the system is greater than the critical micelle concentration (CMC) under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we are interested in the proper formulation of V nel , for which we use an Improved Lennard Jones function (ILJ) that includes an additional parameter (β) with repect to the LJ one [20,21], whose accuracy has been proved by comparing the model predictions with high resolution scattering data [20]. In the last years, the ILJ function has been used to study a high variety of systems, such as small aggregates [22,23,24] or complex systems as those involving nanotubes [25] or clathrates [26,27]. In the parameterization of the ILJ function the relevant parameters ε and r 0 are predicted directly from properties of the partners involved in the system, such as molecular charge distributions and electronic polarizability values.…”
Section: Introductionmentioning
confidence: 99%